13-6n=-5(n-2)+5

Simple and best practice solution for 13-6n=-5(n-2)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-6n=-5(n-2)+5 equation:



13-6n=-5(n-2)+5
We move all terms to the left:
13-6n-(-5(n-2)+5)=0
We calculate terms in parentheses: -(-5(n-2)+5), so:
-5(n-2)+5
We multiply parentheses
-5n+10+5
We add all the numbers together, and all the variables
-5n+15
Back to the equation:
-(-5n+15)
We get rid of parentheses
-6n+5n-15+13=0
We add all the numbers together, and all the variables
-1n-2=0
We move all terms containing n to the left, all other terms to the right
-n=2
n=2/-1
n=-2

See similar equations:

| 2^3x-2=10 | | 13c-7c=24 | | 3(4n+3)=18 | | 5/6x=4/6 | | 12/1=24/x | | 5y+3y=28 | | 3x(x-3)=10x^2-11x | | -2n-n=6(2n-6)-5(3n+6) | | -107=-5(4n+1)+3n | | -4/5-4/3u=-1/2 | | X/2+14=3x | | 7x-3=-8+6x | | 5.32x-12-10x=186 | | j^2–14j+24=0 | | -136=8n-6(8+5n) | | j2–14j+24=0 | | -12+5x+7x2=0 | | 36=5(u-1) | | -42+42x=7(6x-2) | | (X+2)/2=10-(x+5)/3 | | 3(n+4)-8=1/2n | | 4x−8=124x−8+8=12+84x=2044x=204 | | 2(4w-1)=-10(w-3)4 | | 3x^2-9x=10x^2-11x | | 9x+40=6x-2 | | -8/3=1/3u-9/7 | | 5b+6+3=9 | | y+5/4=1/4 | | 750+25x=3,000+10x | | 3200=2x² | | -3/5(20x-5)=-17 | | -(v+7)+1=-2v |

Equations solver categories